Synthesis of an efficient white-light photocatalyst composite of graphene and ZnO nanoparticles: Application to methylene blue dye decomposition - Hossain, Muhammad Mohsin; Ku, Bon-Cheol; Hahn, Jae Ryang (ELSEVIER, 2015)
A graphene-ZnO nanoparticle composite was fabricated by an in situ solvothermal process at low temperatures without catalytic assistance. The as-prepared composite absorbs light at an extended range of wavelengths from the visible to the near IR (400-1665 nm), efficiently absorbs high-intensity light in the near IR region, and exhibits high electrical conductivity. The highly porous structure of aggregated ZnO nanoparticles on the graphene surface enables these particles to absorb dye and degrade it. X-ray photoelectron spectroscopy analysis suggests that a number of oxygen vacancy defects are created in the ZnO matrix and that Zn atoms are chemically bonded to C=0 groups at the relatively amorphous sites of the graphene surface. Raman spectroscopy analysis indicates a strong interaction between the graphene surface and ZnO nanoparticles. Further analyses using scanning electron microscopy, transmission electron microscopy, UV-visible-near-IR absorption, band gap calculations, electrical conductivity measurements, and photocatalysis show that the incorporation of graphene with ZnO nanoparticles narrows the band gap of ZnO, facilitates an extended range of light absorption, improves the electrical conductivity of ZnO, creates oxygen vacancy defects in the ZnO crystal, and enhances stability against photocorrosion. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: CARBON NANOTUBE; THIN-FILMS; CONVERSION-EFFICIENCY; QUANTUM DOTS; OXIDE; NANOCOMPOSITES; PERFORMANCE; DEFECTS; HYBRID; WATER